Administration of intracoronary bone marrow mononuclear cells on chronic myocardial infarction improves diastolic function. Issue 9 (1st April 2008) - Yao, K; Huang, R; Qian, J; Cui, J; Ge, L; Li, Y; Zhang, F; Shi, H; Huang, D; Zhang, S; Sun, A; Zou, Y; et al.
Abstract : Background: Regeneration of the myocardium and improved ventricular function have been demonstrated in patients with acute myocardial infarction (MI) treated by intracoronary delivery of autologous bone marrow mononuclear cells (BMC) a few days after successful myocardial reperfusion by percutaneous coronary intervention (PCI); however, the effects of intracoronary cell infusion in chronic MI patients are still unknown. Aims: To investigate whether intracoronary infusion of BMC into the infarct-related artery in patients with healed MI could lead to improvement in left ventricular (LV) function. Methods: Among 47 patients with stable ischaemic heart disease due to a previous MI (13 (SD 8) months previously), 24 were randomised to intracoronary infusion of BMC (BMC group) and 23 to a saline infusion (control group) into the target vessel after successful PCI within 12 hours after chest pain occurred. LV systolic and diastolic function, infarct size and myocardial perfusion defect were assessed with the use of echocardiography, magnetic resonance imaging (MRI) or 201 Tl single-photon-emission computed tomography (SPECT) at baseline and repeated at the 6-month follow-up examination. Results: BMC treatment did not result in a significant increase in LV ejection fraction in any of the groups by any of the methods used, and the apparent tendency of an improvement was not statistically different between the two groups. The two groups also did not differ significantly in changes of LV end-diastolic and systolic volume, infarct size or myocardial perfusion. However, there was an overall effect of BMC transfer compared with the control group with respect to early/late (E/A) (p<0.001), early diastolic velocity/late diastolic (Aa) velocity (Ea/Aa) ratio (p = 0.002) and isovolumetric relaxation time (p = 0.038) after 6 months, as evaluated by tissue Doppler echocardiography. We noted no complications associated with BMS transfer. Conclusion: Intracoronary transfer of autologous BMC in patients with healed MI did not lead to significant improvement of cardiac systolic function, infarct size or myocardial perfusion, but did lead to improvement in diastolic function.